2017
DOI: 10.1038/srep43617
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Sensing Ion Channel 1a in the amygdala is involved in pain and anxiety-related behaviours associated with arthritis

Abstract: Chronic pain is associated with anxiety and depression episodes. The amygdala plays a key role in the relationship between emotional responses and chronic pain. Here, we investigated the role of Acid-Sensing Ion Channels 1a within the basolateral amygdala (BLA), in pain and associated anxiety in a rat model of monoarthritis (MoAr). Administration within the BLA of PcTx1 or mambalgin-1, two specific inhibitors of ASIC1a-containing channels significantly inhibited pain and anxiety-related behaviours in MoAr rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Youssef et al. showed ASIC1a activation is associated with the PI3K/AKT pathway . Our data showed after treatment with the PI3K/AKT inhibitor LY294002, the ASIC1a expression and [Ca 2+ ] i was significantly induced in PDGF‐induced HSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Youssef et al. showed ASIC1a activation is associated with the PI3K/AKT pathway . Our data showed after treatment with the PI3K/AKT inhibitor LY294002, the ASIC1a expression and [Ca 2+ ] i was significantly induced in PDGF‐induced HSCs.…”
Section: Discussionmentioning
confidence: 99%
“…and Bo Duan et al. showed that PI3K/Akt signalling affects ASIC1a expression and activity via membrane transduction in neurons . This has not been reported in liver fibrosis or HSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated-Plus-Maze (EPM) test. At D29, EPM was performed as previously described 64 . Animals were recorded for 5 min by Mediarecorder software.…”
Section: Behavior Recognition System Phenotyper the Phenotyper (Noldmentioning
confidence: 99%
“…The channels are formed by combinations of ASIC subunits in homo or hetero-trimeric complexes 9 12 , with different subunits conferring distinct properties, exhibiting a broad range of kinetic, ion selectivity and pharmacological properties 13 15 . ASICs are involved in various physiological processes, including synaptic plasticity 16 , 17 , neurodegeneration 15 , and pain sensation 2 , 8 , 18 20 . ASICs therefore have emerged as new potential therapeutic targets in the management of psychiatric disorders, neurodegenerative diseases and pain 2 .…”
Section: Introductionmentioning
confidence: 99%